DEPENDABLE DISCHARGES OF THE UPPER AND MIDDLE DIYALA BASINS (Journal of Engineering, 2010)
The Diyala river is a major tributary of the Tigris river that runs through Iran and Iraq which drains an area of 32600 km2. The catchment area consist of four parts which are the area of the basin above Derbendi-Khan, Upper Diyala, Middle Diyala and lower Diyala. Through the last two decade the water coming to the upstream Derbendi-Khan reduced and this reduction reach to about 35%. This research focusing on the water dependable discharges reached to upper and middle Diyala river basin as compared with Russian study(water balance). The water balance mention that the discharge can be supplied the above basins with probability of 95%for the year (1947-1948). In this research consider the mean discharge down stream Derbendi-Khan dam for the period (1989-2007) in order to find the dependable probability for discharge which can be satisfied and equivalent to the water balance study .In this research considered different probabilities (95%,80% and 50%) of each months (Oct-Sep) water year for the period (1989-2007) by using the empirical Wei Bull probability equation, and it was conclude that the probability of 50% can be considered the suitable probability for the water requirement to upper and middle basins.